Current‐Induced Skyrmion Generation through Morphological Thermal Transitions in Chiral Ferromagnetic Heterostructures. Issue 49 (4th October 2018) - Lemesh, Ivan; Litzius, Kai; Böttcher, Marie; Bassirian, Pedram; Kerber, Nico; Heinze, Daniel; Zázvorka, Jakub; Büttner, Felix; Caretta, Lucas; Mann, Maxwell; Weigand, Markus; Finizio, Simone; et al.
Abstract: Magnetic skyrmions promise breakthroughs in future memory and computing devices due to their inherent stability and small size. Their creation and current driven motion have been recently observed at room temperature, but the key mechanisms of their formation are not yet well‐understood. Here it is shown that in heavy metal/ferromagnet heterostructures, pulsed currents can drive morphological transitions between labyrinth‐like, stripe‐like, and skyrmionic states. Using high‐resolution X‐ray microscopy, the spin texture evolution with temperature and magnetic field is imaged and it is demonstrated that with transient Joule heating, topological charges can be injected into the system, driving it across the stripe‐skyrmion boundary. The observations are explained through atomistic spin dynamic and micromagnetic simulations that reveal a crossover to a global skyrmionic ground state above a threshold magnetic field, which is found to decrease with increasing temperature. It is demonstrated how by tuning the phase stability, one can reliably generate skyrmions by short current pulses and stabilize them at zero field, providing new means to create and manipulate spin textures in engineered chiral ferromagnets. Abstract : Magnetic skyrmions are particle‐like chiral twists of the magnetization with intriguing properties arising from their topology. Thermally driven transitions between different topological phases are studied in heavy‐metal/ferromagnet heterostructures in which skyrmions can be realized at room temperature. Joule heating by nanosecond current pulses can be used to generate stable or metastable skyrmion lattices, as shown experimentally and explained through atomistic simulations.